Voices of the silenced - Gordey, Gordon; Ganert, Dave; Lilley, Stephanie; Kochan, Alexis; Dunn, Maria; Pugh, Ryan (My University, 2013)
Video performance excerpt of a contemporary original dance theatre work titled Voices of the Silenced, conceived and directed by Gordon Gordey. This dancework was created for The Ukrainian Shumka Dancers of Canada. Voices of the Silenced is a contemporary Ukrainian Canadian narrative folk dance theatre work with video exploring the unjust internment of Ukrainian Canadians as “enemy aliens” in Canada during WWI. These “enemy aliens” were subjected to having to carry registration identity papers, often pay monthly registration fees, and were under constant surveillance. Of the 80,000 who were registered under the authority of the Act, 8,579 were deemed: “enemy aliens”. The majority of “enemy aliens” were Ukrainians and were arrested and interned in 26 makeshift encampments located mostly in Canada’s frontier hinterlands. They were forced into hard labour clearing land for roads, building bridges, and building the railway.
Keywords: Canadian War Measures Act of 1914; Ukrainian Shumka Dancers; World War I; Castle Mountain; Banff; Canadian dance; internment camps; contemporary Ukrainian dance; enemy aliens